COMPARISON ON EFFECT OF KETOFOL AND KETOFOL-DEXMEDETOMIDINE COMBINATION ON HYPERDYNAMIC RESPONSES TO MODIFIED ELECTROCONVULSIVE THERAPY AND THEIR ROLE IN AGITATION AND PATIENT’S SATISFACTION - RUTVI M MODY; SONALI A JOSHI; DAISY S GAJJAR; NIDHI S PATKI (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: The aim of our study was to assess the anesthetic effect of combined ketofol-dexmedetomidine on hemodynamics, seizure duration, recovery characteristics, agitation, and patient’s satisfaction following electroconvulsive therapy (ECT) in psychiatric patients. Material and method: A total of 46 patients of the American Society of Anesthesiologists grade I and II were divided into 2 groups. Group A (ketofol group) patients were premedicated with injection glycopyrrolate 0.005 mg/kg IV. Group B (ketofol-dex group) patients were given 0.005 mg/kg IV glycopyrrolate and 0.5 μg/kg dexmedetomidine was infused intravenously over 10 min before induction of anesthesia. Both the groups were induced with injection ketofol for ECT and hemodynamic responses, motor seizure response, recovery profile, agitation score, and patient satisfaction score were observed. Result: The demographic profile was comparable in both groups. Ketofol used was less in ketofol-dex group (81.96±9.26 mg) compared to ketofol group (104.78±10.92mg). Ketofol-dex group has a lower incidence of agitation (1.43±0.59 vs. 2.09±0.60), more patient satisfaction (1.35±0.57 vs. 2.04±0.71), and acceptable decrease in heart rate and blood pressure as compared to ketofol group without any significant side effects. Motor seizure duration was prolonged in ketofol-dex group (39.04±2.67 s) compared to ketofol group (35.04±2.95 s). Conclusion: Dexmedetomidine is effective in attenuating acute hyperdynamic response to ECT without altering seizure duration and recovery from anesthesia, with the added benefit of decreasing post-ECT agitation with more patient satisfaction.